STING Signaling Promotes Apoptosis, Necrosis, and Cell Death: An Overview and Update - Liu, Song; Guan, Wenxian (Mediators of Inflammation, 2018)
STING is a newly identified intracellular sensor of foreign and endogenous DNA. STING has been recognized as an activator of immune responses by TBK1/IRF3 and NF-κB pathways, and it is suggested to play critical roles in host defense, autoimmune diseases, and tumor immunity. Recent studies have revealed that the outcome of STING activation could vary between distinct cell types and scenarios. STING activation in certain cell types triggered cell death including apoptosis and necrosis. This effect could be critical for preventing unnecessary or excessive inflammatory events and maintaining host immune homeostasis. This review is dedicated to summarize recent evidences in the field of STING-mediated cell death and to demonstrate dual outcomes of STING signaling. Besides canonical immune responses represented by IFN and TNF productions, STING signaling can also induce cell death events in a variety of cell types. The double-faced characteristics of STING signaling requires further exploration and precious regulation before tailoring clinical strategies for associated diseases.